Tooth-meshing-harmonic static-transmission-error amplitudes of helical gears. (1st January 2018) - Mark, William D.
Highlights: Fourier series of transmission error is developed using tooth-pair properties. Required properties are tooth-pair modifications/elastic deformations and stiffnesses. Several models of above properties are developed. Model shapes are normalized by contact ratio allowing general applicability. Discontinuities at tooth-contact initiation and termination govern transmission error. Abstract: The static transmission errors of meshing gear pairs arise from deviations of loaded tooth working surfaces from equispaced perfect involute surfaces. Such deviations consist of tooth-pair elastic deformations and geometric deviations (modifications) of tooth working surfaces. To a very good approximation, the static-transmission-error tooth-meshing-harmonic amplitudes of helical gears are herein expressed by superposition of Fourier transforms of the quantities: (1) the combination of tooth-pair elastic deformations and geometric tooth-pair modifications and (2) fractional mesh-stiffness fluctuations, each quantity (1) and (2) expressed as a function of involute "roll distance." Normalization of the total roll-distance single-tooth contact span to unity allows tooth-meshing-harmonic amplitudes to be computed for different shapes of the above-described quantities (1) and (2). Tooth-meshing harmonics p = 1, 2, … are shown to occur at Fourier-transform harmonic values of Qp, p = 1, 2, …, where Q is the actual (total) contact ratio, thereby verifying its importance in minimizing transmission-error tooth-meshing-harmonic amplitudes. Two individual shapes and two series of shapes of the quantities (1) and (2) are chosen to illustrate a wide variety of shapes. In most cases representative of helical gears, tooth-meshing-harmonic values p = 1, 2, … are shown to occur in Fourier-transform harmonic regions governed by discontinuities arising from tooth-pair-contact initiation and termination, thereby showing the importance of minimizing such discontinuities. Plots and analytical expressions for all such Fourier transforms are presented, thereby illustrating the effects of various types of tooth-working-surface modifications and tooth-pair stiffnesses on transmission-error generation.